Utilization of mechanistic modelling and simulation to analyse fenspiride proarrhythmic potency – Role of physiological and other non‐drug related parameters. (6th September 2022) - Wiśniowska, Barbara; Holbrook, Mark; Pollard, Christopher; Polak, Sebastian
Abstract: What is known and objective: Fenspiride, a drug that had been used for decades for the treatment of respiratory diseases, was recently withdrawn from the market due to the potential risk of QT prolongation and proarrhythmia. This is the first such withdrawal for many years and hence poses a question whether such risk could have been predicted and to what degree non‐drug‐specific parameters play a role in the reported QT prolongation and cases of TdP. The study aim was to test various 'what–if' scenarios to assess the influence of age, gender, heart rate, and plasma potassium concentration on QT interval prolongation due to various doses of fenspiride with the use of mechanistic mathematical modelling. Methods: Concentration‐time profiles were simulated with the use of a PBPK model developed based on published physico‐chemical data, data from in vitro ADME experiments, and in vivo PK study results. Pharmacodynamic effect, that is, drug‐triggered pseudoECG signal modification was simulated using a biophysically detailed model of human cardiac myocytes. Analysis of the qNet metric was also performed to classify proarrhythmic risk related to fenspiride. Results: In the simulation study, arrhythmia was not observed even in the 'what–if' scenarios with extreme exposure, age, heart rate, and plasma potassium concentration. The qNet metric value positioned fenspiride in the intermediate risk class. What is new and conclusion: It can be hypothesized that the clinically observed arrhythmia cases were not directly caused by fenspiride alone but a combination of multiple factors, including comedications. Abstract : In this study, we investigated the cardiac risk of fenspiride, the drug that has recently been withdrawn after decades of market presence. In the simulation study using PBPK‐PD model, arrhythmia was not observed even in the extreme conditions in terms of exposure, age, heart rate, and plasma potassium concentration. In addition, qNet metric value positioned fenspiride in the intermediate proarrhythmic risk class. Thus, it can be hypothesized that the clinically observed arrhythmia cases were not directly caused by fenspiride but a combination of multiple factors, including comedications was needed.